Identification of Two New Lactams from the Hulled Seeds of Coix lachryma‐jobi var. ma‐yuen. (25th August 2015) - Han, Ah‐Reum; Kang, Unwoo; Kil, Yun‐Seo; Lee, Jun; Seo, Eun‐Kyoung
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="bkcs10456-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>